Rethinking redistribution: Nancy Fraser and Political Economy - Paternostro Bueno da Silva, Enrico (2018)
Based on Axel Honneth and Nancy Fraser’s controversy about the theory of recognition, the article focuses on the North-American author’s approach to Political Economy. After discussing the given treatment to the issue in her articles that compose Redistribution or recognition, as well as the objections to it, this work seeks to investigate if the subsequent revisions achieved by Fraser were enough and satisfactory to overcome the main limitations and unanswered questions of her critical model.